The role of the Federal Audit Bureau in controlling the advances and their impact on the state budget Applied research in the "Federal Audit Bureau and the Ministry of Finance" - Hanan Abdulameer; Mowaffaq Abdul Hussein (Journal of Madenat Alelem University College, 2018)
Government activity and accounting for operations that occur in the environment of government units require using of intermediate accounts that called advances accounts, as there are elements in the state budget for expenditures that have been fully paid, therefore, it is recorded under the item of public expenditure of the State, according to its chapters and kinds, and here arises the problem of amounts owed to the State during the fiscal year and is not paid to the owners because of the failure to complete the payment procedures, So the use of the accounts of the intermediary is necessarily to control, auditing and recording therefore it appear after the end of the financial year and after making the necessary adjustments from the accounts comprising the final account. The research aims to shed light on the types of advances accounts used in the Government decentralized accounting systemand the procedures for controlling and auditing these accounts. And to know the role of the Federal Audit Bureau in checking the accounts of the advances that have been accumulated in the accounts of the state, and the statement of treatments that would limit the aggravation and accumulation in order to give a clear and accurate picture of the financial position of the state And keep public money from waste and loss, the main findings of the research is the weakness of the Ministry’s role in monitoring the advances and the repayment process Which affected the disclosure process of the Final Account of the State, Continued accumulation of temporary advances funds, Granted to current and investment budget,not to check the accuracy of the settlement of certain advances granted to the State departments,the amounts of advances provided by the Accounting Department are different, for amounts of advances settled in some State administrations, This led to the emergence of advances assets contrary to nature, The Accounting in Department of the Ministry of Finance to disburse cash advances without the allocation covered in the budget of some state departments, Grant some cash advances before the enactment of the State Budget Law, The Ministry of Finance has settle some of the advances granted without allocation through transfer of non-utilized allocations in the budget of the beneficiary administration, Or the allocation of emergency reserves in the budget of the Ministry of Finance, although these fire operations require the existence of legislation.